Evaluation of the Effect of an Aqueous Extract of Azadirachta indica (Neem) Leaves and Twigs on Glycemic Control, Endothelial Dysfunction and Systemic Inflammation in Subjects with Type 2 Diabetes Mellitus – A Randomized, Double-Blind, Placebo-Controlled Clinical Study - Pingali U (Dove Medical Press, 2020)
Usharani Pingali, Mohammed Abid Ali, Srinivas Gundagani, Chandrasekhar Nutalapati Department of Pharmacology and Therapeutics, Nizam’s Institute of Medical Sciences, Hyderabad, Telangana 500073, IndiaCorrespondence: Usharani Pingali Email ushapingali@yahoo.comPurpose: Neem tree (Azadirachta indica) offers different bioactives ranging from pesticides to therapeutic molecules, depending on which part of the plant is used and the extraction methodology and the solvent used. This study was aimed at evaluating the safety and efficacy of a standardized aqueous extract of Azadirachta indica leaves and twigs (NEEM) on glycemic control, endothelial dysfunction, and systemic inflammation in patients with type 2 diabetes mellitus (T2DM).Methods: In this randomized, double-blind, placebo-controlled clinical study (RCT), 80 T2DM subjects, who have already been on standard metformin therapy, received either 125 mg, 250 mg, 500 mg of NEEM or placebo twice daily for 12 weeks. Postprandial blood sugar level (PPBS), fasting blood sugar level (FBS), glycosylated hemoglobin (HbA1c), insulin resistance (IR), endothelial function, oxidative stress, systemic inflammation, IL-6 and TNF-α, platelet aggregation and lipid profile were assessed. Adverse drug reactions, if any, were noted. GraphPad Prism 8 was used to perform statistical analysis.Results: NEEM at the doses of 125, 250, and 500 mg BID significantly reduced PPBS (from 194.4± 14 to 173.1± 12.8mg/dL, 192.3± 17.1 to 161.8± 9.7mg/dL, and 205.9± 7.2 to 159.3± 7.1mg/dL, respectively), FBS (from 119.2± 5.0 to 109.2± 5.7mg/dL, 115.5± 4.4 to 103.7± 4.2mg/dL, and 120.7± 4.2 to 97.3± 3.7mg/dL, respectively), HbA1c (from 6.87 ± 0.4% to 6.64 ± 0.4%, 7.52 ± 0.4% to 6.86 ± 0.3%, and 7.78 ± 0.2% to 6.26 ± 0.4%, respectively), and IR (from 4.5 ± 1.2 to 3.4 ± 0.9, 3.8 ± 1.1 to 2.5 ± 0.6, and 4.6 ± 1.3 to 2.0 ± 0.6, respectively) compared to placebo. Also, NEEM significantly improved endothelial function, decreased oxidative stress and systemic inflammation compared to placebo. The efficacy was significant with all the doses, but no effect on platelet aggregation or lipid profile was observed.Conclusion: NEEM may significantly ameliorate hyperglycemia, endothelial dysfunction, and systemic inflammation, on top of what metformin could do, in subjects with T2DM.Keywords: Azadirachta indica, neem, hyperglycemia, insulin resistance, endothelial dysfunction, type 2 diabetes, metformin